RAB3GAP2 dysregulation in adult T-cell leukemia/lymphoma (ATLL) compared to acute lymphoblastic leukemia (ALL): a molecular perspective - Samira Pourrezaei; Arash Letafati; Ghazale Molaverdi; Mehdi Norouzi; Sayed-Hamidreza Mozhgani (BMC Research Notes)
Abstract Adult T-cell leukemia/lymphoma (ATLL) is a type of blood cancer related to human T-cell lymphotropic virus type 1 (HTLV-1). The principal aim of this study was to investigate cellular processes related to innate immune response, intracellular protein transport, and translational initiation regulation in individuals afflicted with ATLL and Acute lymphoblastic leukemia (ALL). Whole blood samples and peripheral blood mononuclear cells were collected from 10 viral ATLL patients and 10 ALL subjects. Real-time quantitative PCR was then performed to quantify mRNA expression levels of SMC6, FANCM, EIF4H, WDR7, RAB3GAP2, and IFN α/β. The study revealed some distinctions between ATLL and ALL patients. Particularly, RAB3GAP2 level (P = 0.028) was found to be elevated in ATLL patients compared to ALL. Conversely, expression levels of IFN-β (P = 0.31), SMC6 (P = 0.68), WDR7 (P = 0.43), EIF4H (P = 0.38), and FANCM (P = 0.57) were diminished in ATLL patients in contrast to ALL. These proteins play a pivotal role in both translation and immune activation, suggesting a potential correlation between the observed disparities and the virus-mediated progression of cancer. However, it is worth noting that the expression differences in FANCM, EIF4H, SMC6, and WDR7 between ATLL and ALL were minimal. This proposes that the underlying molecular mechanisms governing ATLL and ALL may largely overlap concerning these cellular processes. However, considerable increased expression of RAB3GAP2 was observed in ATLL compared to ALL.